Estimation of blood volume and blood loss in primary total hip and knee replacement: An analysis of formulae for perioperative calculations and their ability to predict length of stay and blood transfusion requirements - Donovan, Richard L. (J Orthop, 2021)
INTRODUCTION: Blood loss continues to be a common surgical risk in total hip (THR) and knee replacements (TKR). Accurate prediction of blood loss permits appropriate counselling of risks to patients, target optimisation and forecasting future transfusion requirements. We compared blood volume formulae of Moore and Nadler, and blood loss formulae of Liu, Mercuriali, Bourke, Ward, Gross, Lisander and Meunier, to assess associations between calculated values with length of stay and transfusion requirements and determine which are useful in contemporary practice. METHODS: We retrospectively studied patients undergoing primary THR and TKR. We collected data on patient demographics, surgical interventions, pre- and postoperative haemoglobin and haematocrit values, length of stay and blood transfusion requirements. Spearman correlation tests and least squares multiple linear regression were performed. RESULTS: 149 THRs and 90 TKRs in 239 patients were analysed over four months. There was a very strong correlation between blood volume formulae. There were multiple very strong and strong associations between blood loss formulae. Bourke correlated significantly to length of stay, and Liu, Mercuriali, Lisander and Meunier correlated for incidence of transfusion. CONCLUSION: Accurate estimation of perioperative blood loss is increasingly important as demand for joint replacement surgery increases in an ageing population. If the primary interest is the association of blood loss and length of stay, Bourke's formula should be preferred. If the primary interest is calculating risk of transfusion, the formulae of Liu or Meunier should be preferred. The formulae of Mercuriali and Lisander are becoming redundant in contemporary practice.